CATCHABILITY AND DIVERSITY OF FISH SPECIES CAPTURED BY GILL NET IN NEW CALABAR RIVER, NIGERIA - Olaniyi Olopade; Henry Eyina Dienye; Ogheneforon Oderhohwo; Nathanael Akinsafe Bamidele (Research Center for Fisheries, 2020)
The aim of this study was to analyze fish species caught by gill nets and fish diversity of the New Calabar River. Three sampling stations were set based on the coverage situation of the river and ichthyofauna associated with gill nets were sampled twice monthly from February to July 2018. A total of 3,251 ﬁsh specimens, representing 11 orders, 15 families, and 28 species, were captured. The order Perciformes was identified as the most abundant representing five families while the remaining had one family each. The fish family Cichlidae was the most represented with seven species, and other notable families were Alestidae, Clupeidae, and Mugilidae, representing three species each. Prominent among the fish caught monthly included Liza falcipinnis, Mugil cephalus, Sarotherodon melanotheron, Sarotherodon galilaeus, Coptodon guineensis, and Sardinella maderensis. The mean catch per unit effort (CpUE) ranged from 3.15±0.2 to 4.85±0.2 kg unit-1 day11. Results of diversity indices revealed that Shannon-Wiener index values varied between 2.64 and 2.82, Simpson diversity ranged from 0.07 to 0.10, and Pielou’s evenness index values ranged from 0.85 to 0.95. The values obtained in this study showed that the status of fish diversity in New Calabar River was stable.